Effects of Sambiloto (Andrographis paniculata) Extract and Spirulina (Spirulina platensis) Administration on Ki-67 Protein Expression in the Colon Epithelial Cells of Plasmodium berghei-infected Mice - Kusmardi, Kusmardi; Ariffandi, Bagas; Lubis, Nadar Sukri; Lestari, Tri Wahyuni; Intan, Putri Reno; Pakpahan, Alfred (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Malaria remains a global health concern and an endemic disease in Indonesia. Sambiloto (Andrographis paniculata) and spirulina (Spirulina platensis) are two potential antimalarial agents which act as antioxidants and antiinflammatories that can suppress morbidities during chronic inflammation in malaria, such as proliferation in the colon. This study aims to investigate the effects of A. paniculata extract and S. platensis administration on Ki-67 expression in medial colon epithelial cells of Plasmodium berghei-infected mice measured by H-score.METHODS: Thirty P. berghei-infected male Swiss-Webster mice were divided into five groups: negative controls (carboxymethyl cellulose/CMC); positive controls (dihydroartemisinin-piperaquine/DHP); A. paniculata extract alone (AP); A. paniculata extract in combination with S. platensis extract (AP+ES); and with S. platensis powder (AP+PS). All mice were infected with P. berghei on day 0. The treatment for each group were given 3 days before infection (D-3) until the day of infection (D0) for 28 days after infection. Colon tissues were processed with immunohistochemistry to detect Ki-67.RESULTS: A difference in Ki-67 expression was observed among the groups (p<0.01). The mean H-score for the CMC control group is 135.503±6.723. The lowest level of Ki-67 expression was observed in the AP+PS group (H-score= 110.941±7.079). AP group did not show a significant difference from the CMC group (p=0.514) and neither did the AP+ES group (p=0.234).CONCLUSION: In conclusion, administration of A. paniculata extract and S. platensis powder lowers Ki-67 expression in medial colon epithelial cells of P. berghei-infected mice.KEYWORDS: malaria, spirulina, Ki-67, Andrographis paniculata, Spirulina platensis